Intention to Use Cryptocurrency in Batam City among Millennials - Marheni, Dewi Khornida; Jofia, Nurul; Candy (Journal of Global Business and Management Review, 2025)
The intention of individuals to use cryptocurrency is influenced by several factors, including financial literacy, herding behavior, and perceived risk. The purpose of this research is to explore how behavioral finance affects the intention to use cryptocurrency. This study employs a quantitative method. The sampling technique used is purposive sampling by distributing questionnaires based on certain criteria. Data is analyzed using the PLS-SEM method. The sample used for testing consists of 401 respondents who use cryptocurrency. The results of the study indicate that herding behavior and perceived risk have a significant influence on the variable of behavioral intention to use cryptocurrency. This research is important because, before deciding to invest in cryptocurrency, it is crucial for millennials to conduct thorough research, consider their individual risk profiles, and not just follow trends.